Validation of the International Index of Erectile Function (IIFE) for use in Brazil Validação do Índice Internacional de Função Erétil (IIFE) para uso no Brasil - Gonzales A.I.* (2013)
Background: The International Index of Erectile Function has been proposed as a method for assessing sexual function assisting the diagnosis and classification of erectile dysfunction. However, IIEF was not validated for the Portuguese language. Objective: Validate the International Index of Erectile Function in patients with cardiopulmonary and metabolic diseases. Methods: The sample consisted of 108 participants of to Cardiopulmonary and Metabolic program Rehabilitation (CPMR) in southern Brazil. The clarity assessment of the instrument was performed using a scale ranging from zero to 10. The construct validity was carried out by confirmatory factor analysis (KMO = 0.85; Barllet p < 0.001), internal consistency by Cronbach's alpha and reproducibility and interrater reliability via the test retest method. Results: The items were considered very clear with averages superior to 9. The internal consistency resulted in 0.89. The majority of items related correctly with their domains, with exception of three questions from sexual satisfaction domain, and one from erectile function. All items showed excellent stability of measure and substantial to almost perfect agreement. Conclusion: The present study showed that the IIEF is valid and reliable for use in participants of a cardiopulmonary and metabolic rehabilitation program.